The effect of column and temperature variation on the determination of the dead time in gas chromatographic systems using indirect methods. Issue 2 (February 2020) - Idroes, Rinaldi; Muslem; Mahmudi; Saiful; Idroes, Ghazi Mauer; Suhendra, Rivansyah; Irvanizam
Abstract: The precise determination of the dead time is essential in a chromatography system as it is a primary parameter for the determination of other secondary parameters such as the adjusted retention time, relative retention time, retention factor and retention index. Several of the indirect methods used for the determination of the dead time in this study were iteration, nonlinear, spreadsheet and statistics methods, which were implemented using the ANSI C programming language. The calculation of each method was tested with temperature and column variations for measuring the retention time of a n-alkane homologous series and accuracy analysis of each mathematical method (indirect method) to the marker substance (direct method). Changes in the temperature and column variations (type, polarity and column length) affected the calculation of the dead time values but did not affect its accuracy. The value of the dead time generated by the non-linear method was relatively high, with errors above 10%, while the other methods utilized are quite good with errors below 8% regardless of the column and temperature variations. Abstract : Analytical chemistry; Chemical engineering; Gas chromatography; Alkanes; Dead time; Column and temperature effect; Mathematical methods